Hedgehog signaling modulates cigarette‑induced COPD development - Lu, Fang; Chen, Rong; Zhou, Min; Guo, Yi (Experimental and therapeutic medicine, 2021)
Hedgehog (Hh) signaling is involved in early embryogenesis and maintains quiescence in the adult lungs. The interruption of Hh signaling may lead to the development of chronic obstructive pulmonary disease (COPD). The current study aimed to assess whether the Hh pathway affects cigarette-induced emphysema and airway inflammation by regulating inflammatory cytokines. C57BL/6J mice were randomized into control, cigarette smoke (CS) or CS + cyclopamine (CSC) groups. Control mice were exposed to normal room air, CS mice were exposed to tobacco smoke and CSC mice were exposed to CS and received cyclopamine treatment. Histopathological examination of lung tissues was performed, and the expression of sonic hedgehog (HH), glioma-associated oncogene homolog 1 (Gli1), hedgehog-interacting protein (HIP) and several inflammatory mediators (intracellular adhesion molecule-1, IL-6, IL-8 and TNF-α) were compared using reverse transcription-quantitative PCR and western blotting. The emphysema of lung tissues by histopathological examination demonstrated partial amelioration in the CSC group compared with that in the CS group. Additionally, expression levels of SHH, Gli1 and inflammatory mediators were significantly higher in the CS group compared with the control group but were significantly decreased in the CSC group. The expression of HIP was decreased in the CS group, but significantly increased in the CSC group. Hh signaling may serve an important role in cigarette-induced emphysema and airway inflammation by regulating inflammatory cytokines in animal models. Therefore, diminishing the activation of the Hh signal may serve as a novel therapeutic strategy for patients suffering from smoking-related COPD.